“Trick or treat”: the influence of incentives on developmental changes in feedback-based learning - Unger, Kerstin; Greulich, Berit; Kray, Jutta (Frontiers in Psychology, 2014)
Developmental researchers have suggested that adolescents are characterized by stronger reward sensitivity than both children and younger adults. However, at this point, little is known about the extent to which developmental differences in incentive processing influence feedback-based learning. In this study, we applied an incentivized reinforcement learning task, in which errors resulted in losing money (loss condition), failure to gain money (gain condition), or neither (no-incentive condition). Children (10-11 years), mid-adolescents (13-14 years), and late adolescents (15-17 years) performed this task while event-related potentials (ERPs) were recorded. We focused our analyses on two ERP correlates of error processing, the error-negativity (Ne) and the error positivity (Pe) that are thought to reflect a rapid preconscious performance monitoring mechanism (Ne) and conscious detection and/or evaluation of response errors (Pe). Participants in all age groups responded more quickly and accurately in gain and loss conditions than in the no-incentive condition. The performance data thus did not support the idea that incentives generally have a greater behavioral impact in adolescents than in children. While the Ne was not modulated by the incentive manipulation, both children and adolescents showed a larger Pe to errors in the gain condition compared to loss and no-incentive conditions. This is in contrast to results from adult studies, in which the Ne but not the Pe was enhanced for high-value errors, raising the possibility that motivational influences on performance monitoring might be reflected in the activity of separable neural systems in children and adolescents vs. adults. In contrast to the idea of higher reward/incentive sensitivity in adolescents, our findings suggest that incentives have similar effects on feedback-based learning from late childhood into late adolescence with no changes in preferences for “trick over treat".